Iranian Illicit Drug Market A Glance at Tehran's Market - Fariborz Raeeis Dana (Drug Control Headquarters, Research and Education Office, 2003)
This article reviews Iranian illicit drug market and also addresses the amount of consumption, type of consuming drugs as well as drug prices in Tehran's market. To examine Iranian drug market, we have reviewed opium prices in Afghanistan and drug transition routes into the I. R. of Iran where some part of transited drugs are exported to Europe and United States of America. Owing to the fact that transited drugs are entering Iran via two border provinces namely Sistan and Baluchistan and Khorassan, and these two provinces have different conditions for drug traffickers, the price and type of transited drugs are varied in each region. In this study, changes in illicit drug prices in entering points (affected by internal situation of Afghanistan), price fluctuations inside the country and main factors of such changes are studied. Meanwhile, factors which influence over prices and their added value are explored on this basis, there is a regression which estimates the number of those who are active in illicit drug supply inside the country by using the rate of arrestees. The performance of anti-drug agencies is also appraised and there would be an estimation of total funds allocated by these agencies to illicit drug campaign, prevention and treatment. As a consequence, it is determined that the average cost spent for per kg of seized drugs is equal to opium average price. Another matter is drug distribution pattern in Tehran that is estimated through a comparative collation between illicit drug prices and some household consuming goods. It shows the rate of consumed drugs by an addict in comparison to consumed goods.Finally, the performance of rehabilitation centers and addicts'conditions icluding gender, education, income, occupation, marital statute and housing in ational as well as Tehran levels are studied.